2017
DOI: 10.1002/brb3.869
|View full text |Cite
|
Sign up to set email alerts
|

Codeine is associated with poor prognosis in acute stroke

Abstract: BackgroundThe aim of this study was to investigate how the use of analgesics, sleeping drugs, and sedatives relates to prognosis and complications in stroke patients in the acute care phase (≤48 hr) after a stroke.Materials and MethodsPatients with ischemic stroke, hemorrhagic stroke, and transient ischemic attack were included. The study is based on gathering of data on medication from 921 patient records belonging to patients included in the Bergen NORSTROKE registry, 12.2009‐02.2012. In this database risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…No previous research has investigated the association between tramadol prescription and the risk of pneumonia, but some studies have linked opioid use to an increased risk of pneumonia (Dublin et al, 2011; Ryste et al, 2017). Among the dwelling elders in the community, patients with pneumonia were 38% more likely to be currently exposed to opioids than matched controls (Dublin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No previous research has investigated the association between tramadol prescription and the risk of pneumonia, but some studies have linked opioid use to an increased risk of pneumonia (Dublin et al, 2011; Ryste et al, 2017). Among the dwelling elders in the community, patients with pneumonia were 38% more likely to be currently exposed to opioids than matched controls (Dublin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Among the dwelling elders in the community, patients with pneumonia were 38% more likely to be currently exposed to opioids than matched controls (Dublin et al, 2011). Another cohort study of acute stroke patients showed that codeine users had 3.8 times the risk of pneumonia compared with codeine‐free opioid users (Ryste et al, 2017). In addition, previous studies have linked an increased risk of respiratory infections to opioids use regardless of immunosuppressive properties (Edelman et al, 2019; Wiese et al, 2018).…”
Section: Discussionmentioning
confidence: 99%